2015
DOI: 10.1007/s00436-014-4300-3
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of regulatory T cells decreases cardiac parasitosis and inflammation in experimental Chagas disease

Abstract: Infection with the protozoan parasite Trypanosoma cruzi may lead to a potentially fatal cardiomyopathy known as Chagas heart disease. This disease is characterized by infiltration of the myocardium by mononuclear cells, including CD4+ T cells, together with edema, myofibrillary destruction and fibrosis. A multifaceted systemic immune response develops that ultimately keeps parasitemia and tissue parasitosis low. T helper 1 and other pro-inflammatory T cell responses are effective at keeping levels of T. cruzi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 82 publications
0
16
2
3
Order By: Relevance
“…Although several studies have shown the involvement of Treg cells in CD [ 28 30 ], the role of Tregs in CD treatment is poorly understood, mainly in the acute phase of the infection with distinct strains. In the acute phase, Tregs probably help to decrease parasitemia and balance inflammatory response [ 56 , 63 ]. Understanding the role of Tregs could help to control the inflammatory response and tissue damage, to reduce the intense Th17 response and autoimune response observed in several infections [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have shown the involvement of Treg cells in CD [ 28 30 ], the role of Tregs in CD treatment is poorly understood, mainly in the acute phase of the infection with distinct strains. In the acute phase, Tregs probably help to decrease parasitemia and balance inflammatory response [ 56 , 63 ]. Understanding the role of Tregs could help to control the inflammatory response and tissue damage, to reduce the intense Th17 response and autoimune response observed in several infections [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that T. cruzi infection resulted in increased IL-10, TGF-beta and Foxp3 expression compared to controls. These results suggest that both strains of T. cruzi can induce Treg and cytokine production associated with this cells [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…T regs play a preponderant role in controlling the immune response in other parasitic infections. In fact, depleting these cells decreases the number of parasites in Chagas’ disease . A number of studies describe some mechanisms for T reg suppressive actions and their effect in parasitic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, deficient signaling of IL-10 correlated with increased mortality in experimental T. cruzi infection due to overwhelming inflammatory responses mediated by TNF and IFNγ ( 21 , 22 ). Depletion of Treg cells in T. cruzi -infected mice leads to reduced cardiac parasitosis and inflammation, accompanied by an augmented Th1 response early in the course of infection followed by a downregulation of this response and increased Th17 response late in infection ( 23 ).…”
Section: Introductionmentioning
confidence: 99%